Cesarean versus Vaginal Delivery: Whose Risks? Whose Benefits? - Gregory, Kimberly D.; Jackson, Sherri; Korst, Lisa; Fridman, Moshe (American Journal of Perinatology, 2012)
We reviewed the risks and benefits of vaginal and cesarean delivery to help frame the inherent trade-offs that should be considered as part of the informed consent discussion between patients and providers. We performed a targeted literature review for common complications of childbirth. Approximately 30% of women will experience a maternal or neonatal complication during childbirth. Both cesarean and vaginal delivery is associated with well-known measurable short- and long-term maternal and neonatal complications and benefits. Childbirth is not risk free. There are data available that can guide the informed consent process with objective quantifiable data that patients and providers can use to weigh risks and benefits of delivery methods.
Keywords: cesarean delivery; labor and delivery complications; informed consent; obstetric quality and safety